2018
DOI: 10.1371/journal.pone.0205661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation, terrain and soil layer depth on eight soil chemical properties and soil fertility based on hybrid methods at urban forest scale in a typical loess hilly region of China

Abstract: Although the spatial mapping and fertility assessment of soil chemical properties (SCPs) are well studied in the Loess Plateau region of China at farmland scale, little is known about spatial mapping the SCPs and their fertility and their influence factors at urban forest scale. The objectives of this study were to (1) compare the performance of two spatial interpolation methods, Ordinary kriging (OK) and regression kriging (RK), and (2) explain the relationships of the vegetation, terrain, and soil layer dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Recently, the evaluation of soil physio-chemical properties increased due to the growing interest in the assessment of management practices, consequences on the quality of soil, sustainability of forest ecosystem functions, and addition to plant production (Schoenholtz et al, 2000). These physio-chemical properties are related to soil fertility and soil productivity including, soil bulk density (BD), porosity, total nitrogen (TN), total phosphorus (TP) and total potassium (TK), available phosphorus (AP), and available potassium (AK), exchangeable cations capacity (CEC), electric conductivity (EC), soil pH, and organic carbon contents (SOC), (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the evaluation of soil physio-chemical properties increased due to the growing interest in the assessment of management practices, consequences on the quality of soil, sustainability of forest ecosystem functions, and addition to plant production (Schoenholtz et al, 2000). These physio-chemical properties are related to soil fertility and soil productivity including, soil bulk density (BD), porosity, total nitrogen (TN), total phosphorus (TP) and total potassium (TK), available phosphorus (AP), and available potassium (AK), exchangeable cations capacity (CEC), electric conductivity (EC), soil pH, and organic carbon contents (SOC), (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization includes rapid increases in population, industrial structure, and landscape varieties (Zhang & Su, 2016). Large-scale LULCC was introduced in Beijing as a result of immediate urbanization from 1975 to 1997, which focused on developmental expansion and the erosion of intrusive agricultural land due to infrastructural changes in the concept of urbanization in the capital area (Zhang & Su, 2016;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…That is, the relationship is relevant to many disciplines, including urban planning, climate change, and environmental monitoring (Carlson & Arthur, 2000;Ogashawara & Bastos, 2012;Rogan & Chen, 2004;Sexton et al, 2013;Weng, Liu & Lu, 2007). LULCC from one type to another, especially from farmland to metropolitan land/built-up areas, influences the process of energy exchange between the terrestrial surface and the atmosphere (Chen et al, 2006;Tonkaz & Çetin, 2007;Zhang et al, 2018). Characterizing the spatial heterogeneity of the urban heat island (UHI) as capable of changing with LULCC in urbanization is very significant for understanding ecosystem functions (Tali et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This method takes into account the extreme value and average value of the assessment object data set [39]. Scholars improved the Nemerow index method to assess soil fertility quality [40]; the results of their studies also indicated that the improved Nemerow index method could reflect the minimum factor law for crop growth in ecology, and it was more rigorous and sensitive than the traditional weighting method for the assessment of soil fertility [37,41].…”
Section: Calculation Of the Sfi And Seimentioning
confidence: 99%